2018
DOI: 10.1001/jamainternmed.2018.0254
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cannabis Legalization in the Opioid Crisis

Abstract: The prescription opioid and heroin crisis: a public health approach to an epidemic of addiction. Annu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
(10 reference statements)
0
7
0
1
Order By: Relevance
“…Students should be cognizant of the changing national and state roles of the pharmacist in laws governing cannabis cultivation, sales, and employment. 52,53 Curricula should also include time to discuss the legal challenges around access to and use of novel, emerging, and/or synthetic psychoactive substances and "designer drugs" (eg, psychedelics, cathinones, synthetic cannabinoids (ie, K2), kratom, illicitly manufactured fentanyl). [54][55][56][57][58] Content related to contemporary statutes and regulations regarding access to, control, and administration of controlled substances, harm reduction equipment, drug paraphernalia, medications for opioid use disorder (ie, buprenorphine, methadone, naltrexone), and opioid antagonists (eg, naloxone access laws) should be included as part of law course curricula.…”
Section: Legal and Ethical Issuesmentioning
confidence: 99%
“…Students should be cognizant of the changing national and state roles of the pharmacist in laws governing cannabis cultivation, sales, and employment. 52,53 Curricula should also include time to discuss the legal challenges around access to and use of novel, emerging, and/or synthetic psychoactive substances and "designer drugs" (eg, psychedelics, cathinones, synthetic cannabinoids (ie, K2), kratom, illicitly manufactured fentanyl). [54][55][56][57][58] Content related to contemporary statutes and regulations regarding access to, control, and administration of controlled substances, harm reduction equipment, drug paraphernalia, medications for opioid use disorder (ie, buprenorphine, methadone, naltrexone), and opioid antagonists (eg, naloxone access laws) should be included as part of law course curricula.…”
Section: Legal and Ethical Issuesmentioning
confidence: 99%
“…One policy considered to impact opioid overdose deaths is increasingly permissive Cannabis legislation [11]. Currently, more than 33 states permit Cannabis use for medical purposes, and 11 states permit recreational Cannabis use [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that approximately 16% of CNCP patients co-use cannabis and prescription opioids (Degenhardt et al, 2015; Sohler et al, 2018). In addition, population health research has found associations between the legalization of medical cannabis and decreases in opioid-related deaths, hospitalizations, and overdoses, as well as reductions in expenditures related to prescription opioid overdose and misuse (Bachhuber, Saloner, Cunningham, & Barry, 2014; Bradford, Bradford, Abraham, & Adams, 2018; Hill & Saxon, 2018; Vyas, LeBaron, & Gilson, 2017). Adverse effects of both short and long-term cannabis use have been documented including, memory impairment, impaired motor coordination, paranoia, psychosis, cognitive impairment and increased risk for anxiety and depression (Volkow, Baler, Compton, & Weiss, 2014).…”
Section: Introductionmentioning
confidence: 99%